2019
DOI: 10.5465/amj.2017.1488
|View full text |Cite
|
Sign up to set email alerts
|

Energizing through Visuals: How Social Entrepreneurs Use Emotion-Symbolic Work for Social Change

Abstract: We know little about how social entrepreneurs try to induce enactment of their cause, especially when this cause is difficult to embrace. Through a longitudinal study, we analyze how anti-plastic pollution social entrepreneurs use multimodal (visual and verbal) interactions to influence their targets and promote their cause. Our findings reveal that these social entrepreneurs used what we call emotion-symbolic work, which involved using visuals and words to elicit negative emotions through moral shock, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(144 citation statements)
references
References 113 publications
(153 reference statements)
7
131
1
5
Order By: Relevance
“…Another data source for this multimodal approach is social media, which is largely used by institutional scholars (e.g. Barberá-Tomás et al, 2019), such as Facebook, Twitter, LinkedIn, and other platforms in which organizational members interact on organizational-level issues. By using multimodal methods, researchers are able to address the limitations of possible memory loss and the difficulty of tracking emotions’ changes over a longer period of time.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another data source for this multimodal approach is social media, which is largely used by institutional scholars (e.g. Barberá-Tomás et al, 2019), such as Facebook, Twitter, LinkedIn, and other platforms in which organizational members interact on organizational-level issues. By using multimodal methods, researchers are able to address the limitations of possible memory loss and the difficulty of tracking emotions’ changes over a longer period of time.…”
Section: Future Directionsmentioning
confidence: 99%
“…Emotional energy as a transitory and collective phenomenon generated between interacting individuals (Collins, 1993) is a growing interest among institutional scholars (e.g. Barberá-Tomás et al, 2019) and the two other categories—organizational process (e.g. Walsh and Bartunek, 2011) and strategizing (e.g.…”
Section: Future Directionsmentioning
confidence: 99%
“…This unexpected outcome-the forgetting of nature-is problematic because it comes in tension with the very objective of carbon accounting which is to account for nature. Recently, organizational scholars have called to reconsider the role of emotions, notably in tackling grand challenges (Barbera-Tomas et al, 2019), as they are "deeply connected to social processes at societal, interorganizational, organizational and interpersonal levels" (Zietsma et al, 2019).…”
Section: Climate Change Is a Systemic And Social Issue -And We Must Nmentioning
confidence: 99%
“…Yet, in the field of social entrepreneurship the effectiveness of visual methods or graphic representations are rarely studied (with the notable exceptions of Barberá-Tomás et al, 2019;and Sparviero, 2019), and not yet organized into a comprehensive framework. In the domain of entrepreneurship, Muñoz et al (2011) found that entrepreneurship students who improved their opportunity-identification mental frames during the course, had a radical shift in the way that they visually represented the concept of entrepreneurship with sketches.…”
Section: Benefits Of Visualizations For Social Enterprisesmentioning
confidence: 99%
“…In this phase they can rely on impactful visualizations such as quasi-realistic scenario drawings, infographics or vivid images and visual metaphors. It is challenging to explain innovative ideas to non-technical public; visual symbols used by activists (Barberá-Tomás et al, 2019) and entrepreneurs (Clarke, 2001) are found to mobilize and energize volunteers, clients, and investors.…”
Section: Idea Promotion and Resources Acquisitionmentioning
confidence: 99%